Moving while you're stuck: a macroscopic demonstration of an active system inspired by binding-mediated transport in biology. Issue 10 (17th February 2021) - Koo, Kanghyeon; Lalitha Sridhar, Shankar; Clark, Noel; Vernerey, Franck; Hough, Loren
Abstract : Demonstrating binding-mediated motion in active polymers using a macroscopic prototype with better design control. Abstract : Diffusive motion is typically constrained when particles bind to the medium through which they move. However, when binding is transient and the medium is made of flexible filaments, each association or dissociation event produces a stochastic force that can overcome the medium stickiness and enable motion. This mechanism is amply used by biological systems where the act of balancing binding and displacement robustly achieves key functionalities, including bacterial locomotion or selective active filtering in cells. Here we demonstrate the feasibility of making a dynamic system with macroscopic features, in which analogous binding-mediated motion can be actively driven, precisely tuned, and conveniently studied. We find an optimal binding affinity and number of binding sites for diffusive motion, and an inverse relationship between viscosity and diffusivity.